Design Thinking in Pedagogy - Luka, Ineta (Journal of Education Culture and Society, 2020)
The twenty-first century has brought lots of challenges for people in all spheres, including education. In the new context, traditional approaches often seem ineffective and therefore new tools and methods have to be applied. An alternative approach that might be useful in the given context is design thinking – the approach that originated in architecture, design and art, and nowadays is applied in many fields. It is a human-centered problem-solving approach that may be used in the teaching/learning process to develop twenty-first century skills and enhance creativity and innovation. This paper introduces readers to the origin of design thinking, its attributes and processes as well as its application in pedagogy.